Generation of mouse induced pluripotent stem cells using polycistronic lentiviral vector in feeder - and serum-free culture - Mahmaud, Akram Faisal (2015)
Somatic cells can be directly reprogrammed into embryonic stem (ES)-like cells by the introduction of several transcription factors. The generated ES-like cells, known as induced Pluripotent Stem (iPS) cells have great potential for regenerative medicine as well as for fundamental and translational research. However, there have been serious concerns regarding the safety of the use of iPS cells clinically. Firstly, the conventional viral-mediated transfer strategy can lead to multiple transgene integrations into the genome of a cell, thus increasing the risk of insertional mutagenesis. Secondly, feeder layers and serumcontaining media are traditionally required for the maintenance of iPS cells. Exposure of the cells to animal products from the media may lead to the risk of xeno contamination. For this reason, the full elimination of animal-sourced ingredients and the use of serum free media are necessary. In this study, a polycistronic lentiviral vector encoding four defined transcription factor genes was used to reprogram mouse tail-tip fibroblasts into iPS cells in a feeder- and xeno-free environment. The generated iPS cells exhibited the (i) morphology and self-renewal properties of ES cells, (ii) expression of ES cell-specific pluripotent markers, and (iii) potential to differentiate into the three major distinct specialized germ layers in vitro. The flow cytometry, immunocytochemistry, and RT-PCR analyses revealed high expression levels of ES cell markers such as Oct4,Nanog, Sox2, Klf4, c-Myc and SEEA-1. The iPS cells were also shown to have the potential to differentiate into neural precursor and neuron cells in culture, with greater than 95% of nestin, Pax6 and βIII-tubulin expression. Although the safety profile of the cells was not analysed, this body of work describes the successful generation of iPS cells from mouse tail-tip fibroblasts without the requirement of serum and a feeder layer.